Refinement of Surgical Procedure and Husbandry Practices of Bile Duct Ligation in Mice Model of Cholestatic Disease (Journal of Laboratory Animal Science, 2022)
Refinement of procedure plays a pivotal role on improving the well-being of laboratory animals that enables successful  outcomes of experiments by obtaining reliable data. In general, identical practices reduce variability among mice and there  may be several factors that can confound results which becomes inevitable within the context of long-term experiments.  We explored several refinements pertaining to surgical techniques and husbandry practices of ongoing studies with the  objectives of reducing early mortality during post-operative period (72h) and ensuring animal welfare as higher priority by  providing better alternative husbandry practices until the termination of experiments. The entire refinement process was  systematically implemented in mice where surgical intervention of bile duct ligation (BDL) was carried out and allowed  to develop liver fibrosis as part of therapeutic requirement then treated with new chemical entities (NCE’s) along with  standard of care (SOC) upto 14 days. Survival surgery involving large number of mice in different groups was approved by  the ethical committee. The notable refinements implemented such as suture patterns along with tissue adhesive to prevent  wound dehiscence; replacement of corncob by adopting paper based bedding with nesting pads as enrichments; provision  of Individually Ventilated Cages (IVC) with top inlet air supply for uniform flow in order to minimize hypothermia. Other  contributing factors which included the use of improved surgical platform with thermo-controlled integral monitoring  systems; Provision of infra-red light source immediately after surgery and until recovery; use of food supplement (Diet  Gel) along with regular rodent diet; clinical scoring of mice during post-operative care and its management. However,  there was no interference on fibrotic disease progression as well as experimental results because these refinements were  implemented in a coordinated manner as part of ongoing process. Collectively, refinements of surgical as well as husbandry  practices have improved the likelihood of mice and reduced incidences of mortality from 35% to 4% of four subsequent  studies conducted at different intervals in mice.
Keywords: essential components; replacement